1992
DOI: 10.1093/ajcn/56.3.543
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the application of the relative-dose-response test for assessing vitamin A status in older adults

Abstract: We investigated the time course and the reproducibility of the relative-dose-response (RDR) test for assessing vitamin A status in older adults. The maximum plasma retinol response to 480 retinol equivalents (RE) of retinyl palmitate in abnormal responses was at 6 or 7 h after dosing compared with the 5-h sampling interval recommended by others for younger adults and children. With respect to reproducibility, the diagnostic concordance of two RDR tests at 7-d intervals in 14 elders was 71%. In 29% of tests, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Whatever the mechanism involved, it is tempting to suggest that this "abnormal" postprandial plasma retinol response is related to the higher fasting plasma retinol concentrations that have been observed in elderly as compared to young subjects in several studies (8)(9)(10). Furthermore, this phenomenon might partly explain why the RDR test is not as reliable in elderly as in young people to detect vitamin A deficiency (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the mechanism involved, it is tempting to suggest that this "abnormal" postprandial plasma retinol response is related to the higher fasting plasma retinol concentrations that have been observed in elderly as compared to young subjects in several studies (8)(9)(10). Furthermore, this phenomenon might partly explain why the RDR test is not as reliable in elderly as in young people to detect vitamin A deficiency (27).…”
Section: Discussionmentioning
confidence: 99%
“…As aging affects numerous physiologic processes, it may directly or indirectly affect vitamin A postprandial plasma transport at different levels: (a) it is possible that the age-related alterations of gastrointestinal tract functions (19)(20)(21)(22) might modify the efficiency of vitamin A intestinal absorption in older subjects; (b) the age-related modification of enterocyte functions might affect the esterification processes of retinol by impairment of either lecithin-retinol acyltransferase (LRAT) or acyl CoA-retinol acyltransferase (ARAT) (23)(24)(25); (c) the plasma transport of retinyl esters from the intestine to the liver is likely affected, as it has been shown that aging delays the clearance of plasma retinyl palmitate (15), but it is not known whether this phenomenon is specific for retinyl palmitate or exists for the other retinyl esters found in the chylomicrons; (d) finally, it is not known if agerelated modification of liver cells (26) or extrahepatic cells functions can affect plasma retinol homeostasis in elderly people, but the low efficiency of the relative dose response (RDR) test in elderly peoples (18,27) to detect vitamin A deficiency suggests that this can be the case.…”
mentioning
confidence: 99%